2000
DOI: 10.1177/120347540000400403
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma of the Skin

Abstract: We identified poor prognostic factors that may necessitate more aggressive treatment. The suggested staging system, incorporating primary tumour size, accurately predicted outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 143 publications
5
99
1
1
Order By: Relevance
“…Five patients (55%) with small tumors (size o2 cm) showed no DNA changes. In compliance with previous studies, 11,25 large tumor size and nodal disease at the presentation had a negative impact on overall survival in MCC patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Five patients (55%) with small tumors (size o2 cm) showed no DNA changes. In compliance with previous studies, 11,25 large tumor size and nodal disease at the presentation had a negative impact on overall survival in MCC patients.…”
Section: Discussionsupporting
confidence: 88%
“…Slight male predominance, mean age 68 years and almost half of the tumors located in the head and neck region. 11,14 During the course of the disease 47% of the patients progressed to metastatic dissemination, local recurrence was recorded in 42% patients. These data are also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cumulative data from small series have suggested that stage, size of the primary tumor, and gender may have an influence on survival, whereas the prognostic impact of anatomic location and age are more controversial. [5][6][7][8] Although various factors can determine the aggressiveness of PNCs, the capacity for invasion and metastasis of tumor cells, involving the degradation of components of basement membranes and the extracellular matrix, is certainly important. The matrix metalloproteinases (MMPs) are a large family of zinc-dependent proteolytic enzymes 9,10 involved in the degradation of different components of the extracellular matrix.…”
mentioning
confidence: 99%